DOI: 10.14264/uql.2015.877
|View full text |Cite
|
Sign up to set email alerts
|

Microbial electrosynthesis from carbon dioxide: performance enhancement and elucidation of mechanisms

Abstract: Microbial electrosynthesis (MES) of organics from carbon dioxide has been recently put forward as an attractive technology for the renewable production of valuable multi-carbon reduced end-products and as a promising CO 2 transformation strategy. MES is a biocathode-driven process that relies on the conversion of electrical energy into high energy-density chemicals. However, MES remains a nascent concept and there is still limited knowledge on many aspects.It is still unclear whether autotrophic microbial bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 241 publications
(478 reference statements)
0
12
0
Order By: Relevance
“…Fermentation 2021, 7, x FOR PEER REVIEW 3 of 38 technology has gained much popularity, it revolves around e − transfer and energy transformation. Researchers are now exploiting the design of electrochemical devices, electrodes, catalyst and separator material optimisation and screening of electroactive microorganisms [2,16,[28][29][30][31].…”
Section: Bioelectrochemical System (Bes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fermentation 2021, 7, x FOR PEER REVIEW 3 of 38 technology has gained much popularity, it revolves around e − transfer and energy transformation. Researchers are now exploiting the design of electrochemical devices, electrodes, catalyst and separator material optimisation and screening of electroactive microorganisms [2,16,[28][29][30][31].…”
Section: Bioelectrochemical System (Bes)mentioning
confidence: 99%
“…Production of organic compounds from MES is considered to be an effective technique for the inception of various beneficial multi-carbon reduced end-products like acetate and butyrate by the valorisation of low-value CO 2 . Further, bio-production dependent on CO 2 is advantageous, as it uses less arable land and freshwater resources, has low CO 2 emissions, no major nutritional supplementation is needed, has excess substrate availability and lastly, chemical bonds can be employed for the storage of excess electrical energy [8,15,16]. Although MES technology is still in its infancy, it has been demonstrated as a promising green alternative for CO 2 sequestration and bioelectrosynthesis of high-valued multi-carbon organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Lab-scale experiments did not enable us to predict the lifetime of the BES materials. Previous studies have shown that, depending on the operating conditions, carbon-based electrodes can last more than five years (McCreery 2008;Jourdin 2015;Yang et al 2016). As there is no real consensus, a lifetime of ten years was chosen in order to maximise the production rate.…”
Section: Inventory and Modelling Of The Coupling Of Bioelectrosynthesmentioning
confidence: 99%
“…b (Desloover et al 2012). c (Jourdin 2015). The capital cost was converted to AUD dollars at a rate of 1.5 AU$ =1 EURO (17/05/2017).…”
Section: Estimated Operational Cost Of Bes (Opex)mentioning
confidence: 99%